NOUN and noun of category - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article deals with the most distinctive features of nouns, all of which have a single general grammatical meaning. Since the noun category has a subject meaning, it indicates the number, quantity of objects, and takes the suffixes of the number category. Nouns, which represent the opposite of singular and plural numbers, try to influence other words in terms of structure, in other words, the verbs and rhymes associated with the nouns are mutually compatible within the number category. Another morphological-structural indicator of nouns is manifested in their association with the article. In the transition of words belonging to another category to the category of nouns, the article becomes the unit that proves that the phenomenon of substantivization.